20 Years of Experience in Office Hysteroscopy: The Largest Retrospective Study in Greece to Date - Orestis Tsonis; Fani Gkrozou; Nabila Iram; Georgios Ntritsos; Evangelos Dimitriou; Alexandros Tzallas; Angelos Daniilidis; Alexandra Papoudou-Bai; Vassiliki Siafaka; Thomas Vrekoussis; Iordanis Navrozoglou; Minas Paschopoulos (IMR Press, 2023)
Background: Office hysteroscopy is a widely-accepted and useful tool in the every-day practice of gynaecologists. Methods: In this 20-year-retrospective study, data originating from 2675 patients who underwent vaginoscopic office hysteroscopy are presented. The Endoscopic Unit is located in the Department of Gynaecology, University Hospital of Ioannina and it is considered one of the busiest public institutions providing care for a large amount of Greek population in Epirus, North-western Greece. Our findings presented in this very first and nationally largest retrospective study, will contribute to the overall scientific knowledge by providing substantial data with regards to hysteroscopy and to epidemiology of endometrial pathology. Results: Common hysteroscopic indication across all age groups was Abnormal Uterine Bleeding (AUB). Predictive characteristics of hysteroscopy in the diagnosis of various conditions were evaluated for these patients in comparison with their histologic report as the gold standard. Comparing hysteroscopic findings with the respective histology reports revealed that in cases of normal endometrium, sensitivity of 60.9%, specificity of 92.1%, Positive Predictive Value (PPV) of 79.07% and Negative Predictive Value (NPV) 82.8% were estimated. Hysteroscopic detection of endometrial polyps demonstrated sensitivity of 92.04%, specificity of 89.1%, PPV of 73.5% and NPV 97.1%. For fibroids, sensitivity and specificity were calculated at 98.5% and 100% respectively, while PPV and NPV at 100% and 99.9%, respectively. For endometrial cancer, the predictive characteristics were estimated at 87.5% and 99.7% with regards to sensitivity and specificity, and 63.6% and 99.9% for PPV and NPV, respectively. Finally, for cases of hyperplasia, hysteroscopy showed sensitivity of 75.0%, specificity of 91.03%, PPV of 11.7% and NPV of 99.5%. Conclusions: To date, this is the largest retrospective study on office hysteroscopy with the use of vaginoscopic approach technique in Greece. This study has been conducted in one of the busiest public gynecologic endoscopic units across Greece. Our findings are consistent with the international scientific evidence, which has proven that hysteroscopy is an efficient and safe method to investigate pathologies within the uterine cavity and in general is accompanied by satisfactory patient acceptance.